Genetic variation for terminal heat stress tolerance in winter wheat - Fu, Jianming; Bowden, Robert L.; Jagadish, S. V. Krishna; Prasad, P. V. Vara (Frontiers in Plant Science, 2023)
In many regions worldwide wheat (Triticum aestivum L.) plants experience terminal high temperature stress in the grain filling stage, which is a leading cause for single seed weight decrease and consequently for grain yield reduction. An essential approach to mitigate high temperature damage is to develop tolerant cultivars using the conventional breeding approach which involves identifying tolerant lines and then incorporating the tolerant traits in commercial varieties. In this study, we evaluated the terminal heat stress tolerance of 304 diverse elite winter wheat lines from wheat breeding programs from the US, Australia, and Serbia in controlled environmental conditions. Chlorophyll content and yield traits were measured and calculated as the percentage of non-stress control. The results showed that there was significant genetic variation for chlorophyll retention and grain weight under heat stress conditions. The positive correlation between the percent of chlorophyll content and the percent of single seed weight was significant. Two possible mechanisms of heat tolerance during grain filling were proposed. One represented by wheat line OK05723W might be mainly through the current photosynthesis since the high percentage of single seed weight was accompanied with high percentages of chlorophyll content and high shoot dry weight, and the other represented by wheat Line TX04M41164 might be mainly through the relocation of reserves since the high percentage of single seed weight was accompanied with low percentages of chlorophyll content and low shoot dry weight under heat stress. The tolerant genotypes identified in this study should be useful for breeding programs to combine different tolerance mechanisms into the same variety for mitigating heat-caused grain yield loss.